Christian Leadership and Stewardship in the Ecological Mission of the Church - Viscka Eirene Daharang (Philosophy Global: International Journal of Christian and Catholic Philosophy, 2025)
The global ecological crisis demands that the church reconsider its calling as a participant in the missio Dei, which encompasses the restoration of all creation. This study aims to examine the concept of eco-missional stewardship as a model of Christian leadership that integrates spirituality, mission, and ecological responsibility. Using a theological-descriptive approach, this study interprets biblical texts and contemporary theological literature to formulate a leadership paradigm oriented toward the care of creation. The results show that stewardship leadership positions Christian leaders as stewards of God's will, guiding the church to live in harmony with creation through love, justice, and sustainability. Leadership rooted in ecological spirituality affirms that caring for the earth is an active expression of faith. Thus, eco-missional stewardship becomes a theological paradigm that expands the church's mission from human salvation to the reconciliation of all creation. These findings contribute to the development of a contextual and environmentally friendly theology of leadership.